2020
DOI: 10.3897/phytokeys.149.48042
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of the vascular plants of Aberdare Ranges Forest, a part of Eastern Afromontane Biodiversity Hotspot

Abstract: The Aberdare Ranges Forest, located in the Central highlands of Kenya, is an isolated volcanic mountain in the East African Rift Valley with unique flora. Despite its refugial importance to rare and endemic plant species, the diversity of plants in the Aberdare Ranges Forest remains poorly understood. The checklist presented here is a collation of data obtained from multiple floristic surveys and from herbarium specimen collections from the forest. A total of 1260 vascular plants taxa representing 136 families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…The most species-rich families are Fabaceae , Rubiaceae , Asteraceae , Orchidaceae , Apocynaceae , Malvaceae and Euphorbiaceae . These results concur with similar studies conducted in other tropical rainforests such as the Coastal forests of Kenya ( Ngumbau et al 2020 ) and the Nandi forests ( Melly et al 2020 ), as well as other forests in the Afromontane archipelago of East Africa such as the Aberdares forests ( Kipkoech et al 2020 ), Agama forest ( Addi et al 2016 ), Afromontane forests of Ethiopia ( Senbeta et al 2014 ), and the Jibat Afromontane forest ( Burju et al 2013 ). Euphorbiaceae , Orchidaceae , and Rubiaceae are the most important families in Taita Hills in terms of species richness, endemism, and conservation status as all of them have substantial numbers in all three categories.…”
Section: Discussion and Conclusionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most species-rich families are Fabaceae , Rubiaceae , Asteraceae , Orchidaceae , Apocynaceae , Malvaceae and Euphorbiaceae . These results concur with similar studies conducted in other tropical rainforests such as the Coastal forests of Kenya ( Ngumbau et al 2020 ) and the Nandi forests ( Melly et al 2020 ), as well as other forests in the Afromontane archipelago of East Africa such as the Aberdares forests ( Kipkoech et al 2020 ), Agama forest ( Addi et al 2016 ), Afromontane forests of Ethiopia ( Senbeta et al 2014 ), and the Jibat Afromontane forest ( Burju et al 2013 ). Euphorbiaceae , Orchidaceae , and Rubiaceae are the most important families in Taita Hills in terms of species richness, endemism, and conservation status as all of them have substantial numbers in all three categories.…”
Section: Discussion and Conclusionsupporting
confidence: 87%
“…An unprecedented rate of extinction may exceed that of species recovery ( Wheeler et al 2012 ) and therefore prompting a crucial need for floristic inventories ( Palmer et al 1995 ). In Kenya, an updated flora checklist of several key areas of biodiversity importance such as Mount Elgon ( Tweedie 1976 ), Shimba Hills ( Luke 2005 ), Kakamega ( Fischer et al 2010 ), Mount Kenya ( Zhou 2017 ), Cherengani Hills ( Mbuni et al 2019 ), Coastal forests of Kenya ( Ngumbau et al 2020 ), Aberdares Ranges Forest ( Kipkoech et al 2020 ), and South and North Nandi forests ( Girma et al 2015 ; Melly et al 2020 ) have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…This study reports high species richness as compared to the previously available checklists ( Bullock 1933 ; Tweedie 1976 ) whose work remain paramount to the current knowledge of Mt Egon. In this study, the highest species-rich family was Asteraceae , which is consistent with other floristic studies of East Africa ( Mbuni et al 2019 ; Kipkoech et al 2020 ; Melly et al 2020 ; Watuma et al 2022 ). Other common high species families, though not in the same sequence of richness, include Poaceae , Orchidaceae , Lamiaceae , and Cyperaceae .…”
Section: Discussionsupporting
confidence: 92%
“…However, their diversity is at high risk of extinction due to overexploitation, climate change, and habitat destruction ( Stévart et al 2019 ). Several floristic studies have been recently reported on mountains with the aim of formulating priority conservation polices ( Mbuni et al 2019 ; Kipkoech et al 2020 ; Watuma et al 2022 ; Zhou et al 2022 ). However, transboundary mountains have encountered prolonged research barriers emanating from ethical and political disputes ( Roga 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the establishment of the Sino-Africa Joint Research Centre of the Chinese Academy of Sciences (SAJOREC) in 2013, and the launch of the project of the Flora of Kenya in 2015, a collaboration between Chinese and Kenyan botanists. So far, the SAJOREC Research Team has conducted floristic studies in numerous plant diversity hotspots [ 55 , 56 , 57 , 58 , 59 ] and discovered 18 new and newly recorded taxa in TEA ( Figure 3 ). Such collaboration will not only promote the understanding and conservation of plant diversity in TEA, but also promote the training of local young taxonomists.…”
Section: Discussionmentioning
confidence: 99%